Analysis of Conjunctival Sac Microbiome in Dry Eye Patients With and Without Sjögren's Syndrome - Song, Hang; Xiao, Kang; Chen, Zhengyu; Long, Qin (Frontiers in Medicine, 2022)
Purpose: To analyze the conjunctival sac microbial communities in patients with Sjögren’s syndrome associated dry eyes (SSDE) and non-Sjögren’s syndrome associated dry eyes (NSSDE), compared with normal controls (NC). Methods: Conjunctival sac swab samples from 23 eyes of SSDE, 36 eyes of NSSDE and 39 eyes of NC were collected. The V3-V4 region of 16S rRNA gene high-throughput sequencing of was performed on illumina MiSeq platform and analyzed using QIIME. Alpha diversity was employed to analyze microbiome diversity through Chao1 and Shannon indexes. Beta diversity was demonstrated by the principal co-ordinates analysis (PCoA) and Partial Least Squares Discrimination Analysis (PLS-DA). The relative abundance was bioinformatically analyzed at the phylum and genus levels. Results: The alpha diversity was lower in patients with dry eye disease (Shannon index: NC vs SSDE: P=0.020, NC vs NSSDE: P=0.029). Beta diversity showed divergent microbiome composition in different groups (NC vs SSDE: P=0.001, NC vs NSSDE: P=0.001, NSSDE vs SSDE: P=0.005). The top 5 abundant phyla were Firmicutes, Proteobacteria, Actinobacteriota, Bacteroidota and Cyanobacteria in all three groups. The top five abundant genera included Acinetobacter, Staphylococcus, Bacillus, Corynebacterium, Clostridium_sensu_stricto_1. The relative microbiome abundance was different between groups. The Firmicutes/Bacteroidetes (F/B) ratio was 6.42, 7.31 and 9.71 in the NC, NSSDE and SSDE group respectively (NC vs SSDE: P=0.038, NC vs NSSDE: P=0.991, SSDE vs NSSDE: P=0.048). Conclusion: The diversity of conjunctival sac microbiome in NSSDE and SSDE patients was diminished compared with NC. The main microbiome at the phylum and genus level were similar between groups, but the relative abundance had variations. The Firmicutes/Bacteroidetes ratio was higher in the SSDE group.